Zerebrale MR-Bildgebung beim malignen Melanom - Breckwoldt, Michael O.; Bendszus, Martin (Der Radiologe, 2015)
Clinical/methodical issueMelanoma is the third leading cancer entity to metastasize to the central nervous system (CNS) after lung and breast cancer. This is often an early event in the disease course and limits survival. Metastasis in the CNS is the cause of death in 10-40 % of melanoma patients and the incidence of brain metastasis is even higher (50-75 %). Cerebral metastases are commonly found in the subcortical white matter. The signal characteristics can vary substantially and may change over time due to hemorrhages or the accumulation of melanin and paramagnetic ions. It is not yet clear whether novel targeted therapies (e.g. immunotherapy and kinase inhibitors) alter imaging characteristics. Also immune-related side effects, such as hypophysitis (in approximately 5 % of patients receiving ipilimumab therapy) or granulomatous disease (neurosarcoid) can occur.Standard radiological methodsMelanoma metastases are usually hyperdense in computed tomography (CT). In magnetic resonance imaging (MRI) T2-weighted (T2-w) fluid-attentuated inversion recovery (FLAIR) and T1-w sequences (with and without i.v. contrast) should be obtained. Coronal and axial imaging planes should be scanned to cross-correlate findings.Methodical innovationsSusceptibility-weighted imaging is a new sensitive method to detect melanoma metastases. Approximately 66 % of melanoma metastases show intratumoral susceptibility signals (ITSS). This sets them apart from other metastases (e.g. lung and breast cancer show less ITSSs, specificity approximately 81-96 %). Diffusion imaging plays no major role in melanoma brain imaging.PerformanceSusceptibility-weighted imaging increases the sensitivity to detect metastases but lacks specificity. Differentiating metastases, microbleeding or calcification can be impossible. It is controversial how to interpret susceptibility signals without correlative signs on other sequences (differential diagnosis: metastasis, microbleeding and calcification).Practical recommendationsCNS metastases are common in melanoma. MRI screening starting in stage IIc should be considered even in asymptomatic patients. Stage IV requires quarterly MRI examinations. Melanotic and amelanotic metastases show different MRI characteristics. The differentiation between metastasis and microbleeding can be impossible and might require a follow-up scan. Susceptibility-weighted imaging increases the sensitivity of metastases detection but lacks specificity. It can help to differentiate between different metastatic entities.